Simulation of gas–liquid flow in a helical static mixer. (1st December 2015) - Zidouni, F.; Krepper, E.; Rzehak, R.; Rabha, S.; Schubert, M.; Hampel, U.
Abstract: CFD simulations using the Euler–Euler approach are performed to model the gas–liquid bubbly flow in a helical static mixer. The model validation work was based on experiments, which are carried out in a column of diameter 0.08 m packed with helical static mixer elements (length 80 mm/diameter 80 mm). Measurements of gas volume fractions, gas velocities and bubble size distributions at several planes within the mixer elements by in-house developed ultrafast X-ray electron beam tomography were taken (Rabha et al., 2015. Chem. Eng. J., 15, 527–540). The predicted axial and radial gas phase distribution considering different mono-disperse bubble sizes (3, 5.8 and 8 mm) is studied and validated against the experimental results. The dependency of non-drag forces on the bubble size was considered. Consequently, the bubble size dependent effects of the non-drag forces on the flow and on the cross–sectional gas volume fraction distribution are shown. Despite obvious shortcomings of the models for this application, some conclusions on the suitability of certain mixer designs for gas–liquid dispersion may be drawn already. The swirling flows created by the twist and turn of the helical mixer elements, which in turn pushes the lighter phase towards the center of the pipe is well predicted and validated. Further investigations have to consider the bubble size distribution e.g. by a population balance model to accurately predict the dispersion of the gas phase within and downstream the helical static mixer. Highlights: CFD simulations using an Euler–Eulerian approach were performed. A monodispersed bubble size distribution was assumed. Experiments applying a fast X-ray tomographical method were performed. Gas volume fraction, gas velocity and bubble size were measured in different planes. The sensitive influence of the bubble diameter in the simulations was shown.